MONITORING LAND SURFACE CONDITION TOWARD PESAWARAN DISTRICT USING WATERSHED SEGMENTATION METHOD - Ida Ayu Puspita Sari; Suhendro Yusuf Irianto (LPPM STMIK Pringsewu, 2020)
This research will produce a segmentation using watershed segmentation. This method will be used to segment the aerial image of an area in Pesawaran district. The image of Pesawaran district that will be taken is an image for the past 5 years, more precisely the image from 2015-2019. The accuracy of this experiment will be tested using a method called ROC (receiver operational characteristics) and studying the changes in the land surface from year to year using watershed segmentation, then the image will change into a color pattern that represents each area such as forest areas and human settlements.